2008
DOI: 10.3324/haematol.12013
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of FDG-PET/CT imaging to guide biopsies in the detection of histological transformation of indolent lymphoma

Abstract: Positron emission tomography using 18F-fluorodeoxyglucose (FDG-PET) has been successfully evaluated in the management of non-Hodgkin's lymphoma (NHL).1-3 Histological transformation (HT) of indolent lymphoma is a dramatic event that occurs in 5-10% of the patients and carries a dismal prognosis.4,5 Previous studies prove that indolent lymphoma entities show a lower FDG uptake when compared with aggressive lymphomas.6-8 We therefore postulated that FDG-PET/CT identifies aggressive transformation sites and can g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
3
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 11 publications
2
75
3
5
Order By: Relevance
“…Other studies using 18 F-FDG in this setting included mixtures of several lymphoma subtypes, and this heterogeneity may have contributed to the lack of consistency of thresholds of highest SUV max or SUV range (9)(10)(11). For example, our median 18 F-FDG highest SUV max for FL (10.9, Table 2) is higher than the threshold of 10 proposed by Schöder et al, excluding indolent lymphoma with a specificity of 81% (9).…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Other studies using 18 F-FDG in this setting included mixtures of several lymphoma subtypes, and this heterogeneity may have contributed to the lack of consistency of thresholds of highest SUV max or SUV range (9)(10)(11). For example, our median 18 F-FDG highest SUV max for FL (10.9, Table 2) is higher than the threshold of 10 proposed by Schöder et al, excluding indolent lymphoma with a specificity of 81% (9).…”
Section: Discussioncontrasting
confidence: 42%
“…At that moment the diagnostic accuracy is optimal; moreover, given the high intraindividual heterogeneity in uptake, PET will be helpful in the decision of where to biopsy. Although no study showed biopsies of all lymph nodes in a patient, we share the opinion that the lymph node with the highest uptake is most likely the transformed lymph node, also considering data showing uptake correlating with aggressiveness (9)(10)(11)16). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of this diagnostic modality required development of new "revised" criteria for treatment response 44 . Although the use of PET/CT in FL is still in its infancy, the available studies suggest that it is of great value in the identification of patients with FL transformation to aggressive lymphoma 45,46 . On the other hand, the initial assumption that the level of FDG accumulation closely correlates with the level of aggressiveness (histologic subtype) of lymphoma was not confirmed 47,48 .…”
Section: Fig 6 Time To Treatment Failure In Fl Patients Treatedmentioning
confidence: 99%
“…Histological transformation of indolent lymphoma occurs in 20 -30% of the patients. Recent study has shown that FDG-PET can be used as an accurate guide for biopsies in suspected transformed tissues (Bodet-Milin C et al, 2008). The standardized uptake value varies considerably in different tumors of the same lymphoma patients, and biopsies should be performed in the site with the maximum standardized uptake value of the whole body (the highest malignancy) that represents the malignancy of the disease (Bodet-Milin C et al, 2008;.…”
Section: Fdg-petmentioning
confidence: 99%